Changes in physical fitness parameters during a competitive field hockey season - Astorino, T. A.; Tam, P. A.; Rietschel, C. R.; Johnson, S. M.; Freedman, T. P. (The Journal of Strength and Conditioning Research, 2004)
Competitive field hockey requires a substantial amount of muscular strength, speed, and cardiovascular endurance. It is unknown how these parameters of physical fitness change between preseason conditioning to postseason recovery. Therefore, Division III female field hockey athletes (n = 13) completed tests of muscular strength, body composition, and maximal oxygen uptake (VO2max) during each phase of their season. Muscular strength was assessed using 1 repetition maximum (RM) leg and bench press tests. Body composition was assessed by anthropometry (skinfolds [SKF]), circumferences ([CC]), and bioelectrical impedance analysis (BIA). Incremental treadmill testing was administered to assess VO2max. Results: VO2max was unchanged during the season, although a trend (p > 0.05) was shown for a higher VO2max during and after the season vs. before the season. Upper- (10%) and lower-body strength (14%) decreased (p > 0.05) during the season. Percent body fat (%BF) from BIA, fat mass (FM) from CC, and body mass index (BMI) were significantly lower (p < 0.05) in-season and postseason vs. preseason. In conclusion, preseason training was effective in decreasing %BF and increasing VO2max, yet muscular strength was lost. Coaches should incorporate more rigorous in-season resistance training to prevent strength decrements. Moreover, these data support the superior levels of muscular strength and leanness in these athletes compared with age-matched peers.